A Chaperone-Like Role for EBI3 in Collaboration With Calnexin Under Inflammatory Conditions - Watanabe, Aruma; Mizoguchi, Izuru; Hasegawa, Hideaki; Katahira, Yasuhiro; Inoue, Shinya; Sakamoto, Eri; Furusaka, Yuma; Sekine, Ami; Miyakawa, Satomi; Murakami, Fumihiro; Xu, Mingli; Yoneto, Toshihiko; et al. (Frontiers in Immunology, 2021)
The interleukin-6 (IL-6)/IL-12 family of cytokines plays critical roles in the induction and regulation of innate and adaptive immune responses. Among the various cytokines, only this family has the unique characteristic of being composed of two distinct subunits, - and -subunits, which form a heterodimer with subunits that occur in other cytokines as well. Recently, we found a novel intracellular role for one of the -subunits, Epstein-Barr virus-induced gene 3 (EBI3), in pro¬moting the proper folding of target proteins and augmenting its expression at the protein level by binding to its tar¬get protein and a well-characterized lectin chaperone, calnexin, presumably through enhancing chaperone activity. Because calnexin is ubiquitously and constitutively expressed but EBI3 expression is inducible, these results could open an avenue to establish a new paradigm in which EBI3 plays an important role in further increasing the expression of target molecules at the protein level in collaboration with calnexin under inflammatory conditions. This theory well accounts for the heterodimer formation of EBI3 with p28, and probably with p35 and p19 to produce IL-27, IL-35, and IL-39, respectively. In line with this concept, another -subunit, p40, plays a critical role in the assembly-induced proper folding of p35 and p19 to produce IL-12 and IL-23, respectively. Thus, chaperone-like activities in proper folding and maturation, which allow the secretion of biologically active heterodimeric cytokines, have recently been highlighted. This review summarizes the current understanding of chaperone-like activities of EBI3 to form heterodimers and other associations together with their possible biological implications.